Vietnam on the road to global integration: Forging strategic partnerships through international security coopertion - Thayer, Carlye Alan (H. : ĐHQGHN, 2017)
This paper focuses on the new hierarchy in Vietnam’s foreign relations embodied by the term strategic partnership. This paper examines Vietnam’s relations with eight major states with a focus on bilateral international security cooperation: the Russian Federation (2001), Japan (2006), India (2007) People’s Republic of China (2008), Republic of Korea (2009), Spain (2009), United Kingdom (2010) and Germany (2011). The paper concludes by considering future strategic partnerships.